Aeroplane headache, mountain descent headache, diving ascent headache.. Three subtypes of headache attributed to imbalance between intrasinusal and external air pressure?. (May 2018) - Mainardi, Federico; Maggioni, Ferdinando; Zanchin, Giorgio
Background: Headache attributed to aeroplane travel (AH) is currently codified in Chapter 10.1.2 of the International Classification of Headache Disorders 3 beta (ICHD 3 beta). After our previous papers, the investigation was enlarged to 200 patients. Material and methods: People affected by AH contacted us by mail and agreed to fill in a detailed anonymous questionnaire that allowed a thorough definition of the headache features. Results: This extended case series allows us to confirm most of the clinical features of AH, reported in our previously published article, and to partially modify others. New results mainly regard the higher occurrence of accompanying symptoms and the presence of a long lasting mild headache phase, usually not exceeding 24 h, that follows the short lasting acute pain, the duration of which has been confirmed as less than 30 min. Moreover, headache attacks identical to those of AH are reported in a portion of patients, triggered by the ascent during free/snorkeling or scuba diving and rapid descent from high mountains. Conclusion: The coexistence of AH with headache triggered by different environmental factors (ascent during free/scuba diving and descent from high mountains) indicates a common causal mechanism, that is, the imbalance between intrasinusal and external air pressure. We propose to classify them together, within Chapter 10 " Headache attributed to disorders of homoeostasis", under a unique heading " Headache attributed to imbalance between intrasinusal and external air pressure" .